Improving the methodology for assessing the debt sustainability of the subjects of the Russian Federation: integrating debt dynamics and GRP - V. A. Sakharova; S. Ye. Demidova (Путеводитель предпринимателя, 2025)
The urgency of developing new methods for assessing the debt sustainability of the subjects of the Russian Federation is due to the need to form a comprehensive understanding of their financial stability in order to make effective management decisions at the regional and federal levels. The current methodology provides an assessment of the solvency of regions and the level of their debt burden, but does not take into account the dynamics of changes in public debt relative to the growth rate of gross regional product (GRP). In accordance with the principles of sustainable borrowing formulated by the International Monetary Fund, the volume of debt obligations should correlate with investment activity, and not only with current budget expenditures. In this regard, improving the methodology for assessing the debt sustainability of regions remains a significant scientific and practical task aimed at ensuring balanced development of territories.